Psychometric performance of the brief Francis scale of attitude towards Christianity (Francis-4) in Mexican university students - Cassiani-Miranda, Carlos Arturo (Journal of beliefs and values, 2022)
The brief Francis scale of attitude towards Christianity (Francis-4) psychometric performance in Mexico is unknown. The objective was to evaluate the dimensionality, homogeneity, gender differential item functioning (DIF), and nomological validity of Francis-4. 1,108 university students between 18 and 60 years of age were evaluated; 80.4% were women (n = 891). CFA was performed with the following fit indicators: chi-square, RMSEA, CFI, TLI, and McDonald’s omega were calculated. For nomological validity, the mean and standard deviation according to gender were compared with Student’s t-test. Gender DIF was quantified with Kendall’s tau-b. The CFA revealed the following goodness-of-fit coefficients: chi-square = 25.45, df = 2, p = .001, RMSEA = .10, 90% CI .07 – .14, CFI = .99, TLI = .99, and SRMR = .01. Cronbach’s alpha of .97 and McDonald’s omega were .97. Scores were significantly higher in women than in men (M = 8.9, SD = 5.4 versus M = 7.6, t = 3.15, p = .002). Kendall’s tau ranged from .07 to .09 indicating absence of gender DIF. Francis-4 is a unidimensional instrument with nomological validity, high internal consistency, and absence of gender DIF. It is recommended to evaluate its performance in other populations.